2001
DOI: 10.1111/j.1346-8138.2001.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Antioxidative Defense System in Papulopustular Acne

Abstract: Acne vulgaris frequently occurs in the second decade of life. The pathogenesis of the disease is multifactorial. In this study, we aimed to investigate the role of reactive oxygen species in inflammation of acne by determining the activity of antioxidant defense enzymes in leukocytes. Fifty-two patients with papulopustular type acne vulgaris and 36 healthy controls were enrolled. The severity of the disease was examined by the Global Acne Grading System, and the activities of superoxide dismutase (SOD), glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 24 publications
(27 reference statements)
3
62
2
Order By: Relevance
“…Many of these investigations have examined the extent to which a potential oxidative stress burden in the skin might be reflected in the blood of acne patients. In a study involving 52 patients with papulopustular acne, researchers reported that blood antioxidant enzyme activities, including superoxide dismutase (SOD) and GSH-Px, were significantly lower vs. controls [30]. Presumably, the decreased activity is a result of the consistent burden of oxidative stress.…”
Section: Contemporary Investigations - Systemic Oxidative Stressmentioning
confidence: 99%
“…Many of these investigations have examined the extent to which a potential oxidative stress burden in the skin might be reflected in the blood of acne patients. In a study involving 52 patients with papulopustular acne, researchers reported that blood antioxidant enzyme activities, including superoxide dismutase (SOD) and GSH-Px, were significantly lower vs. controls [30]. Presumably, the decreased activity is a result of the consistent burden of oxidative stress.…”
Section: Contemporary Investigations - Systemic Oxidative Stressmentioning
confidence: 99%
“…Four major factors contribute to the pathogenesis of acne vulgaris: hyperplasia of sebaceous glands and increased sebum secretion, hypercornification of pilosebaceous duct, abnormal colonization, particularly by P. acnes , and inflammation 1–5 . Recent studies on the aetiopathogenesis of acne vulgaris have focussed on the role of oxygen free radicals and antioxidant enzymes 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D, as an antioxidant agent, would have positive impression on the disease (19,20). It seems that vitamin D makes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) which were found at lower levels in papulo-pustu-lar cases of acne vulgaris by some Authors (21). Other dietary factors like dairy productions have been raised by investigators in terms of the occurrence of acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%